Nucleon structure in a light-front quark model consistent with quark counting rules and data; Physical Review D; Vol. 91, iss. 5 - Gutsche T. Thomas; Schmidt I. Ivan; Vega A. Alfredo; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2015, 2015)
Title screen